(untitled) (Psychology Travelogs, 2021)
The article substantiates that in maintaining the mental health of future professionals during the educational process a significant role is played by psychological services of higher education, whose activities are provided not only by psychologists but also social educators and social workers and aimed at creating conditions for full harmonious development. students, the implementation of their existing and potential personal and professional opportunities. The formative stage of the experimental study of the formation of the readiness of future psychologists to work in the psychological service in higher education institutions is highlighted. According to the results of the observational experiment, it was found that there is a need to improve the training of future psychologists to work in the psychological service in higher education institutions. Therefore, during the formative experiment, the effectiveness of the special course "Peculiarities of training future psychologists to work in the psychological service in higher education institutions" was tested. The effectiveness of the application of the proposed psychological and pedagogical conditions and the developed methodological support of the pedagogical process of psychological and pedagogical conditions for the formation of the readiness of future psychologists to work in the psychological service of higher education institutions. The results of the pedagogical experiment were statistically verified using Pearson’s test. It is proved that students, whose level of readiness for professional activity is high and average, need professional development, realize the importance of interdisciplinary knowledge and the need for independent renewal of knowledge throughout life, are able to creatively solve situational cross-cutting situations and practical professional tasks, effectively use general and professional software, ready for effective teamwork and professional cooperation.